Separation, Hydrodynamics, and Joule Heating Effects in Continuous Annular Electrochromatography. Issue 6 (29th May 2013) - Laskowski, R.; Bart, H.‐J.; Hessel, Volker; Wang, Qi
Abstract First experimental results of the transfer from an analytical batch electrochromatography to a continuous annular electrochromatographic process are presented. In order to study the electrochromatographic effects, hydrodynamics and functionality tests were investigated in a planar reference system. As stationary phase inside the annular gap, an inorganic C8 reverse‐phase monolith prepared by an in situ sol‐gel process was implemented. The generation of Joule heating during the process was determined by a contact‐free thermal camera system. The volumetric flow rates of the electrolyte were detected by a gravimetric contact‐free measurement method. Finally, a mixture of neutral test substances was used to evaluate the continuous separation efficiency and to fractionate the single substances under process‐like conditions. The separation results were detected by an inline UV‐Vis detection cell and the analysis of the single fractions was performed by an analytical electrochromatograph. The results indicate uniform electroosmotic flow as well as successful separation and fractioning of a neutral test mixture.